RUSSIAN INTELLECTUAL POTENTIAL AND TEACHER EDUCATION - Alice P. Valitskaya (Высшее образование в России)
The article is devoted to the modernization problems of national education and is aimed to analyze the system’s ability to achieve the objectives of the development of intellectual potential of the country. The author offers to consider the methodological errors of the educational policy of the last decades: the orientation to the Euro-American economic model; the assignment of secondary and higher education to the service sector and commercialization; the definition of education as a process (standard quantitative parameters of quality, scientometrics in the ranking ofscientific personnel, and others), the loss of valuable meanings in the content of education, the speculative replacement of the main ideological mission of education with a set of competences - the destruction of teacher education. These errors led to a crisis of the system, and a way out of this crisis is possible only with a radical reform of teacher education, providing an ideological position and a clarity of values.